Nanoparticle assembly enabled by EHD-printed monolayers - Porter, Benjamin Francis (Microsyst Nanoeng, 2017)
Augmenting existing devices and structures at the nanoscale with unique functionalities is an exciting prospect. So is the ability to eventually enable at the nanoscale, a version of rapid prototyping via additive nanomanufacturing. Achieving this requires a step-up in manufacturing for industrial use of these devices through fast, inexpensive prototyping with nanoscale precision. In this paper, we combine two very promising techniques—self-assembly and printing—to achieve additively nanomanufactured structures. We start by showing that monolayers can drive the assembly of nanoparticles into pre-defined patterns with single-particle resolution; then crucially we demonstrate for the first time that molecular monolayers can be printed using electrohydrodynamic (EHD)-jet printing. The functionality and resolution of such printed monolayers then drives the self-assembly of nanoparticles, demonstrating the integration of EHD with self-assembly. This shows that such process combinations can lead towards more integrated process flows in nanomanufacturing. Furthermore, in-process metrology is a key requirement for any large-scale nanomanufacturing, and we show that Dual-Harmonic Kelvin Probe Microscopy provides a robust metrology technique to characterising these patterned structures through the convolution of geometrical and environmental constraints. These represent a first step toward combining different additive nanomanufacturing techniques and metrology techniques that could in future provide additively nanomanufactured devices and structures.